Photography as Cinematic Ekphrasis: Intermedial Study in Garin Nugroho’s Opera Jawa - Wibisono, Sony (Harmonia: Journal of Arts Research and Education, 2023)
The Opera Jawa (2006), directed by Garin Nugroho is an Indonesian film with unique hybridity of art media (music, dance, visual art installation, acting, photography). This study aims to provide an overview of photographic ekphrasis’s form, process, and function. This research used a descriptive qualitative method. Data collection was through observation with the note-taking documentation technique. Through intermedial studies, data analysis was carried out using Agnes Petho’s cinematic ekphrasis and photo-filmic theory. The results of the study show that Opera Jawa displays the characteristics of intermedial reference media through cinematic ekphrasis of photography in film. This matter is manifested at the diegetic media level through family photos of the character Setyo-Siti, and the extra-diegetic media through photographic frames introducing film characters. Cinematic Ekphrasis works with exchange strategies and crossing the borders of basic media modalities (material, sensory, space-time, semiotic) from film to photography. Cinematic ekphrasis ultimately forms a metaphor that mediates the experience and knowledge of film audiences toward the target media and the source media. Thus, Opera Jawa, as the target media, can offer its ideology as a result of Sinta Obong’s source media interpretation.